Merlot grape processing technology for making wines of controlled origin at shabo terroir - Элдар Жораевич Иукуридзе (ScienceRise, 2015)
presents the research on the influence of technological features of processing of grapes Merlot, resulting in founding that the pre-sorting of grapes, separation of ridges, maceration, malolactic fermentation at installed in the enterprise mode allows to receive high quality wine. In view of the data it has been developed technological instruction for production of wine "Merlot Shabo"